Carbazole Alkaloids from Clausena anisum-olens: Isolation, Characterization, and Anti-HIV Evaluation - Yang, Jing-Hua; Wang, Xin-Yi; Zhou, Yi-Ping; Lu, Rong; Chen, Chin-Ho; Zhang, Meng-Han; Cheng, Yung-Yi; Morris-Natschke, Susan L.; Lee, Kuo-Hsiung; Wang, Yun-Song (Molecules (Basel, Switzerland), 2019)
Two new carbazole alkaloids (1,2) and six known carbazole alkaloids (3–8) were isolated from Clausena anisum-olens. Their structures were elucidated based on extensive spectroscopic analysis. All isolated compounds (1–8) were evaluated for their anti-HIV effects on virus replication in MT-4 lymphocytes infected by HIV-1NL4-3 Nanoluc-sec virus, and new carbazole alkaloid 1 exhibited anti-HIV activity with an EC50 value of 2.4 μg/mL and SI of 7.1.